SUBTITUSI AGAR-AGAR DALAM PEMBUATAN JELLY DRINK CINCAU HIJAU (Cyclea barbata) UNTUK MENURUNKAN SINERESIS - Hardoko, Hardoko; Tajuddin, Khoirul Jamhari (Universitas Pelita Harapan, 2019)
Grass jelly (Cyclea barbata) is often processed into jelly products obtained through extracts of water from the leaves, but the resulting jelly has a high syneretic power so that the product becomes runny and is easily damaged. The purpose of this study was to determine the amount of agar (Gracilaria sp.) That can be substituted so as to produce green jelly drink with good character. The method used is an experimental method with the substitution treatment of agar 0, 10, 20, 30, 40% w / w on green grass jelly solution. The results show that increasing the amount of substituted agar decreases the power of syneresis, increases viscosity, increases pH, and decreases the power of jelly drink suction. An increase in agar substitution up to 20% also increases overall preferences or consumer acceptance, but substitutions above 20% tend to reduce the level of jelly drink preference. Thus the best green grass jelly drink is substituted with 20% agar.